The world-system of academic capitalism: Process of consolidation of the entrepeneurial university El sistema-mundo del capitalismo académico: procesos de consolidación de la universidad emprendedora - Eduardo Fernández (Arizona State University, 2009)
The goal of this article is to analyze two institutional contexts in which academic communities develop their educational activities: the enterprising university and academic capitalism. The methodology of analysis of Higher Education institutions in the world system uses the model developed by the sociologist Immanuel Wallerstein. This analysis focuses on three dimensions: the "consolidation of the world-economy of the academic capitalism" (the transformation of higher education as a commodity), the "de-capitalization of the public university" (the new policies of quasi-market and of financing associated with the "entrepreneurial university") and "geoculture of the system-world of the academic capitalism," linked to the society of the knowledge, managerial ideologies, and intellectual entrepreneurship, but also to counter-hegemonic ideologies that supports the autonomy of the university as a pre-condition for social development. Este trabajo reflexiona respecto de dos contextos institucionales que enmarcan la investigación y la actividad docente universitaria: la universidad emprendedora y el capitalismo académico. La metodología de análisis utilizada parte del análisis de los sistemas-mundo del sociólogo Immanuel Wallerstein, y describe el funcionamiento de las instituciones de Educación Superior en el marco general de un sistema mundial de capitalismo académico. El análisis se centra en tres dimensiones: la "consolidación de la economía-mundo del capitalismo académico" (es decir, la transformación de la educación superior en un mercado), la «descapitalización de la universidad pública» (las nuevas políticas de cuasi-mercado y de financiamiento asociados con la "universidad emprendedora") y la "geocultura del sistema-mundo del capitalismo académico", vinculada a la sociedad del conocimiento, la ideología empresarial y al intelectual emprendedor, pero también a otras ideologías contrahegémonicas o de quienes mantienen una defensa de la autonomía universitaria como condición para el desarrollo social. Palabras clave: capitalismo académico; políticas de educación superior; reformas educativas.